A modification on velocity terms of Reynolds equation in a spherical coordinate system. (March 2019) - Askari, E.; Andersen, M.S.
Abstract: The widely-used Reynolds equation to simulate fluid lubrication in hip implants by Goenka and Booker has velocity terms accounting just for the rotational motion of the femoral head. The present study, therefore, hypothesizes that modifying velocity terms being used in Reynolds equation, which capture both translation and rotation of the femoral head, can affect resultant fluid pressure, fluid-film thickness and friction force. To assess such hypothesis, a computational model of a hip implant based on multibody dynamics methodology and Reynold equation is developed. It is illustrated that modifying velocities can cause friction forces to increase, significantly, compared to Goenker and Booker's. Moreover, the minimum film thickness and maximum fluid pressure undergo notable decreases during the swing and stance phases, respectively. Highlights: Velocity terms in Reynold equation for spherical joints were modified. Modified velocity terms affected fluid-film lubrication in hip implants significantly. A notable increase in friction forces was observed using modified velocities. A considerable decrease in minimum film thickness was illustrated during the swing phase. Maximum fluid pressure decreased during the stance phase using modified velocities.